2022
DOI: 10.53986/ibjm.2022.0008
|View full text |Cite
|
Sign up to set email alerts
|

Reducing bacterial antibiotic resistance by targeting bacterial metabolic pathways and disrupting RND efflux pump activity

Abstract: Antibiotic resistance is a significant issue for the medical community, worldwide. Many bacteria develop drug resistance by utilizing multidrug resistant or MDR efflux pumps that can export antibiotics from bacterial cells. Antibiotics are expelled from bacteria by efflux pumps a part of the resistance nodulation division (RND) family. Types of RND efflux pumps include the AcrAB-TolC tripartite protein pump. There are an excessive number of antibiotic compounds that have been discovered; however, only a few an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
0
2
0
1
Order By: Relevance
“…The antibacterial mechanism of MA is from our research, as shown in Figure 15 . As antibiotic resistance has become the global challenge threating people’s health, and many pathogenic bacteria export antibiotics from intracellular environment through developing their multidrug efflux pumps system, which can be induced or evolved under long term excessive drug stress by modifying or regulating relative genes in plasmids [ 30 ], it is very urgent to develop new drugs or adjuvants to overcome antibiotic resistance. In this study, the multi-mechanical actions against S. aureus by MA were systemically verified, indicating that MA is a promising natural compound for controlling S. aureus infection.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial mechanism of MA is from our research, as shown in Figure 15 . As antibiotic resistance has become the global challenge threating people’s health, and many pathogenic bacteria export antibiotics from intracellular environment through developing their multidrug efflux pumps system, which can be induced or evolved under long term excessive drug stress by modifying or regulating relative genes in plasmids [ 30 ], it is very urgent to develop new drugs or adjuvants to overcome antibiotic resistance. In this study, the multi-mechanical actions against S. aureus by MA were systemically verified, indicating that MA is a promising natural compound for controlling S. aureus infection.…”
Section: Discussionmentioning
confidence: 99%
“…на гени, які регулюють метаболізм бактерій і генерують активність ефлюксної помпи, може змінити стійкість до антибіотиків [26]. Ці підходи дають можливість створювати інноваційні агенти, які можуть вибірково та ефективно блокувати ефлюксний насос [14].…”
Section: матеріали та методиunclassified
“…In Silico Molecular Docking Simulation. Studies of docking simulations were carried out to identify the binding pattern of the synthesized compounds (16)(17)(18)(19)(20)(21)(22)(23)(24) to selected protein target active sites (i.e., DNA gyrase B, PqsA, pyruvate kinase, LuxS, and human peroxiredoxin 5) [56]. e binding affinity, hydrogen bond, and amino acid residual interactions (hydrophobic/π-cation/π-anion/π-alkyl and van der Waals interactions) of ligands (16)(17)(18)(19)(20)(21)(22)(23)(24) and standards are presented (SI Tables 7-11).…”
Section: In Silico Admet Prediction Swissadme Is a Web-mentioning
confidence: 99%